Expert opinion survey on medication error awareness, reporting and its challenges among nursing leaders in India - Gonchigar Eswarappa, Shashikala; Agarwal, Akhil; S., Renukaprasanna; Ali Khan, Rashid (International Journal of Research in Medical Sciences, 2025)
Background: Medication errors (MEs) remain a significant concern in healthcare settings globally, particularly in India, where Nurses play a vital role in preventing MEs. This expert opinion survey explored the experience of nursing leaders in handling and reporting of MEs. Methods: This expert opinion study was based on a descriptive survey conducted among 51 nursing leaders from top corporate hospitals in India. The survey consisted of 15 questions covering four key areas: (1) frequency and types of errors, (2) barriers to error reporting, (3) department-related factors, and (4) training/education. Responses were collected through an online self-administered questionnaire between June and November 2024. Results: Most of the nursing leaders (96%) reported encountering MEs. Among them, 39.2% of respondents observed MEs weekly, while 19.6% encountered these errors daily. The common types of errors included prescribing errors (71%), dispensing errors (69%), wrong dosages (63%), and wrong timing (61%). Notably, 37% of nursing leaders perceived underreporting of MEs. Identified barriers to MEs reporting included extra time for documentation (47%), fear of blame (45%), lack of knowledge (47%), absence of anonymous reporting systems (33%), and inadequate information for reporting errors (31%). A significant proportion of respondents (86%) emphasized the need for more comprehensive training to improve ME reporting practices. Conclusions: This survey highlighted the need for transformative changes in ME awareness and reporting in hospitals. Establishing blame-free, anonymous reporting systems and enhancing training are essential. Additionally, advanced technological solutions should be utilized to support nursing staff in improving patient safety via prevention of MEs.